Evaluating a theory-based intervention for improving eHealth literacy in older adults: a single group, pretest–posttest design - Sun Ju Chang; Kyoung-eun Lee; Eunjin Yang; Hyunju Ryu (BMC Geriatrics, 2022)
Abstract Background The Internet is considered an important channel for providing health information to older adults. We developed an intervention to improve eHealth literacy in older adults according to the information-motivation-behavioral skills (IMB) theory and Intervention Mapping. This study aimed to analyze the effect of a developed intervention on information, motivation, behavioral skills, and behaviors related to eHealth information in older adults. Methods Forty-six older adults over the age of 65 were recruited from two senior welfare centers in a city in South Korea. We divided the participants into four groups and conducted one intervention per group from March to December 2019. One intervention consisted of 5 sessions and was performed once a week (2 h/1 time) for 5 weeks, culminating in a total lecture time of 10 h. One lecture instructor and two assistant instructors supported the participants in the computer practices. Results Participants’ computer/web knowledge, perceived ease of use, perceived enjoyment, and attitude toward eHealth information showed statistically significant increases. The eHealth literacy efficacy score, searching performance score, and understanding score were also significantly increased. However, there was no significant difference in perceived usefulness. Conclusion The application of the current theory-based methodology can improve the quality of research in eHealth literacy. Additionally, various interventions should be developed and continuously applied to improve eHealth literacy among older adults.